Male Sex Workers’ Strategies to Manage Client-Related Risks of Violence - Siegel, Karolynn (Journal of interpersonal violence, 2023)
A substantial minority of men who have sex with men (MSM) engage in the exchange of sex for money, drugs, shelter, or material goods. This work carries risks for violence, sexual assault, and other kinds of harm such as robbery and threatening behavior by clients. Yet limited research has focused on the strategies that male sex workers (MSWs) use to prevent or manage these risks. To gain more insights into this matter, we analyzed qualitative interview data from 180 MSM recruited from eight U.S. cities who engaged in sex work with clients they had primarily met through dating/hookup websites and apps. Participants described the strategies they used to manage risks of interpersonal violence, both prior to meeting their clients and at the time of their encounters. Many of the strategies used ahead of the encounter relied upon information and communication technologies, such as negotiating the parameters of the exchange encounter, screening clients, sharing information about the client and meeting place with others, identifying safe meeting locations, and gathering information from social networks about problematic clients. Strategies employed during the encounter included: receiving payment up front; being prepared to protect oneself with a weapon or self-defense techniques; staying alert and sober; and planning an exit route from the location. Technology-based interventions through dating/hookup apps could play an important role in providing resources and skill building for MSWs to help them protect themselves during sex work.